Comparative Anatomical Studies on Shoulder Girdle of Pigeon Hawk (Falco columbarius) and Kite (Millvus migrans) - John, M. A.; Choudhury, A. R.; Khan, M.; Ahmad, K.; Baba, M. A.; Dar, F. A.; Rafiq, A. (Indian Journal of Veterinary Anatomy, 2018)
The aim of the present study was to compare morphological features of shoulder girdle bones in pigeon, hawk and kite. Bones were collected by maceration technique. Shoulder girdle comprised of scapula, coracoid and the clavicular bones in both species. The proximal end of bones of shoulder girdle enclosed a foramen triosseum in both the species. Presence of sub-acromial foramen in scapula of kite was a noteworthy feature, whereas that of pigeon hawk was characterized by a pneumatic foramen just behind coracoid process. A piercing type of foramen was characteristic in the coracoid of kite. The coracoid of pigeon hawk was featured with an additional small pneumatic foramen just behind acro coracoid process. The clavicular bones of pigeon hawk and kite, except the design of foramina, were almost identical. The linear and clockwise arrangement of foramina in the clavicle of pigeon hawk, as compared to the randomly designed foramina of the clavicle of kite, was a characteristic feature.